Learning and memory impairments in a neuroendocrine mouse model of anxiety/depression - Darcet, Flavie; Mendez-David, Indira; Tritschler, Laurent; Gardier, Alain M.; Guilloux, Jean-Philippe; David, Denis J. (Frontiers in Behavioral Neuroscience, 2014)
Cognitive disturbances are often reported as serious incapacitating symptoms by patients suffering from major depressive disorders. Such deficits have been observed in various animal models based on environmental stress. Here, we performed a complete characterization of cognitive functions in a neuroendocrine mouse model of depression based on a chronic (4 weeks) corticosterone administration (CORT). Cognitive performances were assessed using behavioral tests measuring episodic (novel object recognition test, NORT), associative (one-trial contextual fear conditioning, CFC) and visuo-spatial (Morris water maze, MWM; Barnes maze, BM) learning/memory. Altered emotional phenotype after chronic corticosterone treatment was confirmed in mice using tests predictive of anxiety or depression-related behaviors. In the NORT, CORT-treated mice showed a decrease in time exploring the novel object during the test session and a lower discrimination index compared to control mice, characteristic of recognition memory impairment. Associative memory was also impaired, as observed with a decrease in freezing duration in CORT-treated mice in the CFC, thus pointing out the cognitive alterations in this model. In the MWM and in the BM, spatial learning performance but also short-term spatial memory were altered in CORT-treated mice. In the MWM, unlike control animals, CORT-treated animals failed to learn a new location during the reversal phase, suggesting a loss of cognitive flexibility. Finally, in the BM, the lack of preference for the target quadrant during the recall probe trial in animals receiving corticosterone regimen demonstrates that long-term retention was also affected in this paradigm. Taken together, our results highlight that CORT-induced anxio-depressive-like phenotype is associated with a cognitive deficit affecting all aspects of memory tested.